2013
DOI: 10.1177/0194599813490892
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Adenotonsillar Size for Prediction of Severity of Obstructive Sleep Apnea and Flow Limitation

Abstract: Tonsil/adenoid size did not predict the severity of AHI. Nevertheless, adenoid size might be related to lowest oxygen saturation, which is thought to be related to subjective symptoms. Although flow limitation was related to tonsil size but not to QOL in the control group, further research will be needed to understand the importance of flow limitation and upper airway resistance syndrome in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
3
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 24 publications
1
33
3
5
Order By: Relevance
“…In the current investigation, prevalence of severe OSA increased as the grade of tonsil size increased; however, it is important to note that prevalence of residual OSA was not different between the grades of tonsil size. The correlation between adenoid size and OSA has been reported with conflicting results . Our findings showed no difference in the prevalence of severe OSA among the grades of adenoid size.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In the current investigation, prevalence of severe OSA increased as the grade of tonsil size increased; however, it is important to note that prevalence of residual OSA was not different between the grades of tonsil size. The correlation between adenoid size and OSA has been reported with conflicting results . Our findings showed no difference in the prevalence of severe OSA among the grades of adenoid size.…”
Section: Discussioncontrasting
confidence: 63%
“…The correlation between adenoid size and OSA has been reported with conflicting results. 34,35 Our findings showed no difference in the prevalence of severe OSA among the grades of adenoid size. The prevalence of residual OSA increased as the grade of adenoid size decreased.…”
Section: Discussioncontrasting
confidence: 48%
“…6,13 Hypertrophied tonsils may represent one of the several possible etiolo- be aware of the limitations of using these grading scales and must consider parental reports of nighttime snoring and presence of other associated obstructive symptoms in order to diagnose OSA in children. A potential limitation is our intraobserver reliability methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Another major reason is the lack of availability of sleep labs with the ability and desire to test. 22,23 By contrast, it has been reported that clinical history and physical examination are not reliable for diagnosing OSA and that questionnaires alone do not provide a good diagnostic prediction for OSA in children. 23 Consequently, many researchers have tried to find a screening tool for the presence and severity of OSA in children.…”
Section: Discussionmentioning
confidence: 99%